Artificial intelligence model with human-computer brain interaction for virtual communication in patients with disabilities of mobilization and oral communication (SCIÉNDO INGENIUM, 2024)
This research work presents the proposal of an artificial intelligence model with human brain-computer interaction for virtual communication. Characteristics, advantages and disadvantages of application are determined. It is concluded that it is possible to develop a Brain-Computer Interface prototype to achieve virtual communication in people unable to communicate. For this, apart from the 3 phases: registration of brain signals, extraction of characteristics and translation into actions; a feedback from the user is included; and as a methodology, a match of activities was used.
Keywords: artificial intelligence; IBC; virtual communication; brain-computer interaction; computer interface